Limits of high-pressure hydrogen jet combustion in argon power cycle-based energy systems - Chitsaz, Iman; Kakoee, Alireza; Ahammed, Sajid; Salahi, Mahdi; Andwari, Amin Mahmoudzadeh; Ahmad, Zeeshan; Hyvönen, Jari; Mikulski, Maciej (Elsevier, 2026)
This study investigates boundaries of ultra-high pressure (300 bar) hydrogen direct injection in a closed-loop argon power cycle, including combustor and working fluid management subsystems. An integrated 1D–3D CFD framework is implemented to assess the effects of key system parameters on combustion phenomenology under real-world operational constraints of a large-bore, medium-speed engine representative of future extrapolated hydrogen power generation systems. The framework is thoroughly validated with experimental data, including measurements of argon-diluted hydrogen jet ignition from a spray-combustion chamber. Simulations confirm that ignition delay is governed by oxygen entrainment and in-cylinder temperature. Three interacting phenomena driving combustion are also identified: rapid premixed burn of residual or entrained hydrogen; mixing-controlled heat release driven by jet momentum and piston interaction; and late-stage decay limited by liner-suppressed momentum loss. The latter phenomenon leads to diffusion flame quenching, which is difficult to overcome through injection calibration or mixture dilution alone. Combustion efficiency above 92% is essential to prevent early-stage pressure rise rates from exceeding the 10 bar/°CA limit, even though recirculated unburned hydrogen has minimal impact (<0.2%) on indicated efficiency. Increasing the injector discharge coefficient or reducing argon/oxygen circuit pressure support more complete combustion, but both measures introduce trade-offs with excessive peak pressure and thermodynamic efficiency respectively. The best observed trade-off at 90% argon and lambda 1.3 is achieved at hydrogen SOI of −20 CA, with moderate discharge and yields thermodynamic efficiency of 51%, below expected targets. The study's flat piston limits mixing during late combustion, so further gains require injector/bowl geometry co-optimisation.
Keywords: Argon power cycle; Hydrogen; High-pressure direct injection; Jet ignition; Combustion efficiency; Large-bore engine; fi=Energiatekniikka|en=Energy Technology|; fi=Energiatekniikka|en=Energy Technology|; fi=Energiatekniikka|en=Energy Technology|; fi=Energiatekniikka|en=Energy Technology|; fi=Energiatekniikka|en=Energy Technology|